Pengaruh Kepercayaan Merek, Brand Ambassador dan Word of Mouth Terhadap Keputusan Pembelian: (Studi pada Konsumen Produk Kosmetik Wardah di Kota Semarang) - Puspanada, Vianandra Intan; Widyasari, Suzy (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2024)
The purpose of this study is to analyze the influence of brand trust, brand ambassadors and word of mouth on purchasing decisions. The population of this study was consumers of Wardah cosmetic products in Semarang City and the sampling technique used the purposive sampling method, which is a sampling method based on special considerations with a sample of 100 respondents. Data retrieval techniques by distributing questionnaires through google forms. Research instrument tests include validity tests and reliability tests. The validity test was carried out using factor analysis techniques while the reliability test used Cronbach's alpha techniques. Furthermore, data analysis used multiple linear regression tests, determination coefficient tests (R2), f tests and t tests processed using IBM SPSS 26. The results of this study show that partially brand trust, brand ambassadors and word of mouth have a positive and significant effect on purchasing decisions.